Centering Culture in Public Engagement on Climate Change. Issue 5 (3rd July 2020) - Munshi, Debashish; Kurian, Priya; Cretney, Raven; Morrison, Sandra L.; Kathlene, Lyn
ABSTRACT: Much of the communication efforts on climate change has focused on disseminating scientific projections of climate change to galvanize people into responding to the physical, natural, and biological changes being wrought on the planet by human actions. Yet, this dominant approach of public engagement has been limited because groups of people experience climate change in different ways and have very different approaches to respond to its impacts and implications, depending on their own specific cultural contexts. Arguing for a greater emphasis on culture in climate communication, we construct a culture-centered framework for a deliberative approach to public engagement on climate change. This framework is built around the four domains of Values, Place, Power, and Narrative, and illustrates how meaningful communication and action on climate change requires attention to interactions with each of these four domains. The framework has the potential to reframe environmental communication on climate change by highlighting the specific contexts of people's lived experiences.